Trace Elements Reconnaissance in the Lower Coleen River Valley, Upper Yukon Division, Alaska - White, M. G. (Geological Survey (U.S.), 1950)
Abstract: "The highest radioactivity value obtained in a traverse of shales in the Middle Paleozoic section of the lower Coleen River is 0.003 percent equivalent uranium. Traverses on pre-Cambrian schists at Rabbit Mountain were made with negative results."